Ultraviolet/Visible Quasicylindrical Waves on Semimetal Cd3As2 Nanoplates. Issue 4 (17th January 2022) - Xue, Zhaohang; Zheng, Wenzhuang; Li, Yaolong; Xue, Mengfei; Hu, Aiqin; Chen, Junyan; Jia, Shangtong; Tang, Jinglin; Chen, Jianing; Du, Jinlong; Gao, Peng; Ren, Mengxin; et al.
Abstract : Resolving the photonic modes in real space is essential to understand the fundamental process and control of photonic behavior in optoelectric devices. However, the understanding of the photonic modes of semimetal Cd3 As2 is still lacking. Herein, the quasicylindrical waves (QCW) on Cd3 As2 nanoplates using photoemission electron microscopy (PEEM) are found out. The QCW is due to the optical field scattered by subwavelength indentations, with wavelength being the same as the incident light, and their amplitude decays as r −1/2 from the edges. The transverse magnetic (TM) mode dominates the observed QCW of Cd3 As2 nanoplates, which is affected by the edge structure. In broadband from UV to visible, the QCWs on Cd3 As2 nanoplates are observed. Further, nanostructures to achieve subwavelength focusing and interference lattice of the Cd3 As2 optical QCW are achieved. These findings demonstrate the regulation of QCW, which benefits optimizing the optoelectronic performances of semimetal materials in the future. Abstract : The quasicylindrical waves (QCWs) on Cd3 As2 nanoplates using the photoemission electron microscopy (PEEM) are explored. In broadband from UV to visible, the QCWs on Cd3 As2 nanoplates are observed. Further, nanostructures to achieve subwavelength focusing and interference lattice of the QCW are designed. These findings demonstrate the regulation of QCW, which benefits optimizing the optoelectronic performances of semimetal materials.